Video atlas of advanced minimally invasive surgery - Frantzides, Constantine T.; Carlson, Mark A. (Saunders/Elsevier, 2013)
Brings you the visual guidance and expertise you need to master the important and minimally invasive procedures and the treatment of unusual surgery cases. This title includes photographs, DVDs, and online narrated procedural videos.